Prediction of Antioxidant Capacity of Thai Vegetable Extracts by Infrared Spectroscopy - Prommajak, Trakul; Kim, Sang Moo; Pan, Cheol-Ho; Kim, Sang Min; Surawang, Suthat; Rattanapanone, Nithiya (CHIANG MAI UNIV, 2015)
The antioxidant capacity of extracts from 33 local Thai vegetables was determined by ABTS, DPPH, FRAP and FCRC assays. The extracts had a wide range of antioxidant activities and could be categorized into three groups: high, moderate and low antioxidant activities. The antioxidant activities of the four different assays were highly correlated (r > 0.98). Fourier transform infrared (FTIR) spectra and partial least square (PLS) regressions were used to predict the measured antioxidant capacities. The adjusted R-2 was higher than 0.97 for prediction models and higher than 0.89 for cross-validation models, which could be applied on liquid extracts or freeze-dried extract. FTIR spectroscopy in combination with PLS regression successfully predicted the antioxidant capacity of several Thai vegetables.
Keywords: CIOCALTEU REDUCING CAPACITY; PHENOLIC-COMPOUNDS; MEDICINAL-PLANTS; FLAVONOIDS; PREVENTION; CHEMISTRY; DISEASES; ASSAYS; FRUIT; HERBS